Online Information on Antioxidants: Information Quality Indicators, Commercial Interests, and Ranking by Google - Aslam, Romaan; Gibbons, Daniel; Ghezzi, Pietro (Frontiers in Public Health, 2017)
The idea that antioxidant supplements can prevent or cure many diseases is extremely popular. To study the public understanding of antioxidants on the Web we searched the term “antioxidants” on Google.com and analyzed 200 websites in terms of typology (news, commercial, professional, health portal, no-profit or government organization, scientific journals), disease or biological process mentioned (aging, immunity, neurological disease, diabetes, arthritis etc.) and stance towards antioxidants, whether neutral, positive or negative. Commercial and news websites were prevalent (over half of the total) but not in the top 10 returned by Google, where the most frequent were health portals, government and professional websites. Among the diseases mentioned, cancer was the first, followed by vascular and eye diseases. A negative stance toward supplements was prevalent in the whole search and this was even more evident for cancer. Information on aging or immunity had the largest proportion of pro-supplement and commercial websites This study shows that some diseases are highly associated with antioxidants on the Internet and that information on antioxidants in aging and immunity is more likely to describe the positive effects of antioxidant supplements.